Methods and techniquesComparison of radiation dose exposure in patients undergoing percutaneous coronary intervention vs. peripheral intervention - Arif, Salech; Bartus, Stanislaw; Rakowski, Tomasz; Bobrowska, Beata; Rutka, Joanna; Zabowka, Anna; Tokarek, Tomasz; Dudek, Dariusz; Dubiel, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Most endovascular techniques are associated with patient and personal exposure to radiation during the procedure. Ionising radiation can cause deterministic effects, such as skin injury, as well as stochastic effects, which increase the long-term risk of malignancy. Endovascular operators need to be aware of radiation danger and take all necessary steps to minimise the risk to patients and staff. Some procedures, especially percutaneous peripheral artery revascularisation, are associated with increased radiation dose due to time-consuming operations. There is limited data comparing radiation dose during percutaneous coronary intervention (PCI) with percutaneous transluminal angioplasty (PTA) of peripheral arteries. Aim : To compare the radiation dose in percutaneous coronary vs. peripheral interventions in one centre with a uniform system of protection methods. Material and methods : A total of 352 patients were included in the study. This included 217 patients undergoing PCI (single and multiple stenting) and 135 patients undergoing PTA (in lower extremities, carotid artery, renal artery, and subclavian artery). Radiation dose, fluoroscopy time, and total procedural time were reviewed. Cumulative radiation dose was measured in gray (Gy) units. Results: The total procedural time was significantly higher in PTA (PCI vs. PTA: 60 (45–85) min vs. 75 (50–100) min), p < 0.001. The radiation dose for PCI procedures was significantly higher in comparison to PTA (PCI vs. PTA: 1.36 (0.83–2.23) Gy vs. 0.27 (0.13–0.46) Gy), p < 0.001. There was no significant difference in the fluoroscopy time (PCI vs. PTA: 12.9 (8.2–21.5) min vs. 14.4 (8.0–22.6) min), p = 0.6. The analysis of correlation between radiation dose and fluoroscopy time in PCI and PTA interventions separately shows a strong correlation in PCI group (r = 0.785). However, a weak correlation was found in PTA group (r = 0.317). Conclusions : The radiation dose was significantly higher during PCI in comparison to PTA procedures despite comparable fluoroscopy time and longer total procedure time in PTA. Fluoroscopy time is a reliable parameter to control the radiation dose exposure in coronary procedures. The increasing complexity of endovascular interventions has resulted in the increase of radiation dose exposure during PCI procedures.